O sujeito e o gozo escópico na sociedade contemporânea conectada - Lemos, Patrícia do Prado Ferreira (2014)
This research proposes to interface psychoanalysis and society, focusing on the contingencies of late capitalism which cross social linkings and are reflected on the subjects. In view of this situation, we understand the internet takes a notable role, when regarding social networking, by displaying the constitutions of social linkings and some aspects of the structure of these subjects. Thus, the thesis we have seeked to defend is that in the present conjuncture, especially in light of its technological apparatuses, the subjects are more significantly captured by a distinctive modality of gaze, one we apprehend being the "scopic", which in face of its features, exposes the peculiarities of the subjects structures and their interface with other subjects and objects. For such a task, we have divided our research into three complementary chapters: in the first, we investigate different readings about contemporary culture, contrasting between modern and post-modern conceptions and shedding some light on the society in which the subjects are taking part; in the second chapter, we highlight some theoretical differences introduced by Psychoanalysis, presenting the peculiarities of the structure of the subjects, along with some contributions by psychoanalytic authors, regarding the debates around subjects in our society; Finally, in the third chapter, we contemplate our objectives and examine the notion of "scopic field", highlighting the implications on subjects by this modality of gaze, especially in light of social networks. We chose Facebook site as the main social network under investigation, taking it as a device which represents some of contemporary cultural constitutions. We finally stress how subject's structures and language's transhistoricism relate to the forms of gaze implementation and the discursive diversity of social linkings, showing that historical shifts do affect the subjects, but not in its structure